Svp j'ai besoin d'aide pour ces equations:

1) 3(2-3x)-(4+5x) = 0
2) : (x-6) ( 2x-3) = 0


Sagot :

WIAMMI

Réponse :

3(2-3x)-(4+5x) = 0

6 - 9x -4 -5x = 0

2 - 14x =0

-14x = -2

x = 2/14

x = 1/2

(x-6) ( 2x-3) = 0

x-6 = 0                                      2x-3 = 0

x = 6                                           2x = 3

                                                    x = 3/2

Bonjour

1). 3(2-3x) - ( 4+5x) = 0

6-9x - 4-5x = 0

-14x + 2 = 0

-14x = =-2

x = 2/14 = 1/7

2) (x-6)(2x-3) = 0

(x-6) = 0 => x = 6

(2x-3) = 0 => x= 3/2

Bonne journée.